Influence of parenting styles on academic motivation and performance amongst undergraduate students in China - Hu, Qing Qing (2021)
This research is conducted on the basis of previous research.This study discusses the relationship between parenting styles, the academic motivation and academic performance of the undergraduate students.It is helpful to improve the Parenting styles (PS), cultivate and improve the Academic Motivation (AM) and Academic Performance (AP) of the undergraduate students, and promote their physical and mental health. Therefore, the relationship among PS, AM and AP of undergraduate is worthy of research and discussion. The respondents for the survey are 287 questionnaires for the undergraduate students from a university in Zhengzhou, China. This study used the relevant analysis and regression analysis methods for analysis and testing. The research results are sorted out and discussed, hoping to make efforts to improve the AP of the undergraduate students. The results is the Emotion Warmth Parenting Style (EWPS) has a significant positive influence on AP of undergraduate students. The Over-protection Parenting Style (OPS) has a significant negative influence on AP of undergraduate students. The Rejection Parenting Style (RPS) has a negative influence on AP of undergraduate students. The EWPS has a significant positive influence on Academic Motivation to Pursuing Success (AMPS) of undergraduate students.The EWPS has a significant negative influence on Academic Motivation to Failure Avoidance (AMFA)of undergraduate students.The OPS has a significant positive influence on AMPS of undergraduate students. The father ’s OPS has no significant influence on AMFA of undergraduate students. The mother’s OPS has a significant positive influence on AMFA of undergraduate students.The RPS has a negative influence on AMPS of undergraduate students.The RPS has a significant positive influence on AMFA of undergraduate students. The AMPS has a significant positive on AP of undergraduate students. The AMFA has a significant negative on AP of undergraduate students. The partial mediating effect of AMPS on the relationship between the PS and AP. The partial mediating effect of AMFA on the relationship between the PS and AP.